2020
DOI: 10.1016/j.hroo.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of subcutaneous implantable cardioverter-defibrillator performance in patients with ion channelopathies from the EFFORTLESS cohort and comparison with a meta-analysis of transvenous ICD outcomes

Abstract: Background The subcutaneous implantable cardioverter-defibrillator (S-ICD) is an alternative to conventional transvenous ICD (TV-ICD) therapy to reduce lead complications. Objective To evaluate outcomes in channelopathy vs patients with structural heart disease in the EFFORTLESS-SICD Registry and with a previously reported TV-ICD meta-analysis in channnelopathies. Methods The EFFORTLESS registry includes 199 patients with channelopathies (Bru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The study found similar S-ICD efficacy and a reduced incidence of inappropriate shocks in channelopathy patients compared to those with structural heart disease. Similar rates of inappropriate shocks were achieved with S-ICD programming set to higher rates for channelopathy patients [ 136 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 71%
“…The study found similar S-ICD efficacy and a reduced incidence of inappropriate shocks in channelopathy patients compared to those with structural heart disease. Similar rates of inappropriate shocks were achieved with S-ICD programming set to higher rates for channelopathy patients [ 136 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 71%
“…Therefore, some researchers underline the importance of meticulous pre-implant screening, and in some specific situations (for example in Brugada syndrome) — they advise performing an exercise test and pharmacological provocation tests [ 21 , 22 ]. Careful screening allows avoiding future inappropriate interventions to a reasonable extent, and in the comparative analysis of S-ICDs and T-ICDs in that patient population, the efficacy of S-ICD was comparable to T-ICD with the benefit of a lower risk of lead failure [ 23 ]. One should mind though that in some channelopathies (e.g., LQTS 2) associated with bradycardia, the need for pacing may occur, especially in case of therapy with beta-blockers.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in 13 genes have been traditionally associated with LQTS: among those, mutations in potassiumchannel genes KCNQ1 (LQT1 locus) and KCNH2 (LQT2 locus) and the sodium-channel gene SCN5A (LQT3 locus) are the most common causes of the LQTS and account for approximately 75% of cases 30 . Once diagnosis is made, risk stratification is mandatory to tailor lifestyle changes and to deliver the adequate therapy, such as implantable cardioverter defibrillator J o u r n a l P r e -p r o o f (ICD) in high-risk patients, with the modern subcutaneous ICD potentially being the most appropriate therapeutic option [31][32][33][34][35] . All LQTS patients, regardless of the SCD risk, should avoid QT-prolonging drugs, promptly correct electrolyte abnormalities (hypokalemia, hypomagnesaemia, hypocalcemia) that may occur during diarrhea, vomiting or metabolic conditions and avoid genotype-specific triggers for arrhythmias (strenuous swimming, especially in LQTS1, and exposure to loud noises in LQTS2 patients) 36 .…”
Section: Non Modifiable Risk Factorsmentioning
confidence: 99%